EVOLUTION OF THE UNIVERSE ACCORDING TO THE NEW COSMOLOGICAL THEORY - Dokukin, Mikhail; Indyk, (Revista Inclusiones, 2020)
The urgency of the issue under study is dictated by the constant interest in the knowledge of the surrounding Universe by mankind. The purpose of this article is to develop, consistent with experimental data of the cosmological theory, the evolution of the Universe. We believe that the leading approach to the attainment of this purpose is natural-scientific, regular and consistent consideration of this cosmological issue. Starting from the basic provisions of the General Theory of Relativity (which mathematical basis is the equations of A. Einstein), in this paper we analyze the well-known solutions of those equations in the light of cosmological theories development. Special focus is on the analysis of the modern theory of the Big Bang, in particular - its capabilities and limitations. The article deals with a fundamentally new cosmological approach to describing the Universe structure and its evolution. The main provisions of the proposed theory of a steady-state and dynamic Universe are determined, and the fundamental characteristics of the elements in its structure and the features of such elements motion are calculated. It should be emphasized that this theory, which is developed in the methodological plan in accordance with the philosophical principle of succession and conformity by N. Bohr, is good coherent with the well-known astronomical observations, and allows us to draw logical conclusions about the evolution of the Universe just to be guided by fundamental physical laws. The aspects of this article may be useful in both studying the issue under consideration based on the historical perspective, and interpreting the latest results in the study of the Universe.